Analysis of Excavated Soil Utilization as Embankment Material and Foundation Layer on Singaraja – Mengwitani Road Section (BALI) - Dinul Hadi; Ria Asih Aryani Soemitro; Trihanyndio Rendy Satrya; Noor Fachrie (Departemen Teknik Sipil, Institut Teknologi Sepuluh Nopember, 2025)
Road and bridge construction of the Bts. Singaraja City - Mengwitani is located in a tightly contoured hilly area, resulting in a very large volume of excavation and embankment work. Referring to the data from the field inspection of the construction work package, the soil layer in the excavation work has the potential to be used as fill material and foundation layer. This can be a solution to reduce the use of natural materials by utilizing waste materials. This research aims to analyze the utilization of excavated soil on the National Road Bts. Singaraja City - Mengwitani. The research was conducted by identifying the physical and mechanical parameters of the excavated soil at the location of the disposal area, then examining the requirements of the general specifications of bina marga for road and bridge construction in 2018 revision 2, if it does not meet the stabilization using lime to improve the soil parameters to achieve optimal conditions. If the test specimen meets the requirements as backfill soil, then modeling will continue using the Plaxis 2D auxiliary program to calculate the maximum height of safe backfill soil. Based on the results, the excavated soil was classified as silty sand (SM) with plasticity index varying from 5.84% to 12.63%, and CBR values varying from 6.60% to 10.12%. For the material requirements check, all excavated soils meet the requirements as ordinary backfill material, some rest area disposal sites meet the requirements as preferred backfill material, swamp backfill, and graded material backfill, and all excavated soils do not meet the requirements of foundation layer. From the modeling results of the excavated soil parameters obtained, the safe embankment height can reach 3-5 meters.